Measuring Work Fatigue on Nurses: A Comparison between Indonesian Version of Fatigue Assessment Scale (FAS) and Japanese Industrial Fatigue Ressearch Commite (JIFRC) Fatigue Questionnaire - Iwan Muhamad Ramdan (Jurnal Keperawatan Padjadjaran, 2019)
A Nursing is one type of jobs that is at risk of experiencing fatigue because its workload is quite high. Fatigue Assessment Scale (FAS) and Japanese Industrial Fatigue Research Committee (JIFRC) fatigue questionnaire are two instruments that are often used to measure work fatigue in various types of work because the ease of use. This study aims to test and compare the validity and reliability of the Indonesian version of FAS and JIFRC among nurses in one governmental hospital in East Kalimantan Indonesia. The study was conducted on 170 nurses in one of the Class A Referral Government Hospitals in East Kalimantan. Determination of the study sample using stratification simple random sampling method, the FAS questionnaire obtained from Zuraida & Chie, the JIFRC questionnaire was taken from Tarwaka, the Validity and Reliability test using Pearson Product Moment and Cronbach’s alpha. The JIFRC in Indonesian version has a satisfactory psychometric property with adequate validity and reliability to assess work fatigue in nursing profession. The best Cronbach alpha (0.921) will be obtained if item number 3 and 16 are corrected for the editorial/sentence arrangement